Highly efficient palladium-catalyzed cross-coupling of diarylborinic acids with arenediazoniums for practical diaryl synthesis. Issue 7 (13th February 2020) - Wang, Fengze; Wang, Chen; Sun, Guoping; Zou, Gang
Graphical abstract: Highlights: Cost-effective arylboron reagent. Good functional group compatibility. Low loading of simple ligandless catalyst. Mild, open-flask and base-free conditions. High efficacy to heteroatom ortho -substituted diazoniums. Abstract: A highly efficient cross-coupling of cost-effective diarylborinic acids with both isolatable and latent arenediazoniums, i.e. tetrafluoroborates and aryltriazenes, respectively, has been developed with a practical palladium catalyst system under base-free conditions in open flask at room temperature. A variety of electronically and sterically various biaryls, in particular, those bearing a coordinative ortho -substituent, could be obtained in good to excellent yields by using 0.3 mol% palladium acetate as catalyst. Features of the protocol including cost-effectiveness of diarylborinic acids, efficacy to heteroatom ortho -substituted substrates and high chemoselectivity to aryl chlorides have been clearly demonstrated in practical synthesis of fungicide Boscalid.